Luminescent performances of Mn4+ ions during the phase evolution from MgTiO3 to Mg2TiO4. (January 2017) - Long, Jiaqi; Ma, Chaoyang; Wang, Yuzhen; Yuan, Xuanyi; Du, Miaomiao; Ma, Ran; Wen, Zicheng; Zhang, Jiantao; Cao, Yongge
Graphical abstract: Highlights: In this work, TiO2−x MgO: 0.1 at% Mn 4+ (1 ≤ x ≤ 2) red phosphors are synthesized. Luminescent performances of Mn 4+ ions during the phase evolution are studied. The parameter Dq of crystal field in Mg2 TiO4 : Mn 4+ and MgTiO3 : Mn 4+ is calculated. The quenching concentration in Mg2 TiO4 : Mn 4+ and in MgTiO3 : Mn 4+ are compared. Abstract: TiO2−x MgO: 0.1 at% Mn 4+ (1 ≤ x ≤ 2) red phosphors are synthesized through a traditional high temperature solid-state reaction method. The excitation and emission spectra indicate that 700 nm and 660 nm red emission peaks are ascribed to Mn 4+ ions doped in MgTiO3 and Mg2 TiO4, respectively. The Ti 4+ octahedron is connected in MgTiO3 by O 2− ions of the octahedrons, while the Ti 4+ octahedron is separated in Mg2 TiO4 by Mg 2+ tetrahedron and Mg 2+ octahedron. This results that the quenching concentration is higher in Mg2 TiO4 than in MgTiO3 leading the less luminous centers in MgTiO3 . Detailed spectroscopic and crystal-field studies of the Mg2 TiO4 : Mn 4+ and MgTiO3 : Mn 4+ is described in the present paper.